Stress reduction interventions: A scoping review to explore progress toward use of haptic feedback in virtual reality - Brelet, Lisa; Gaffary, Yoren (Frontiers in Virtual Reality, 2022)
This present review focuses on traditional reduction-stress interventions and on reduction-stress interventions in virtual reality. Two main methods of stress reduction are explored: relaxation techniques and meditation techniques. Relaxation techniques achieve a state of no tension through a control and a reduction of physiological activity. Meditation techniques also achieve a relaxation response but additionally increase sustained attention on the moment present and on oneself. However, this review also notes the limitations of traditional techniques such as training or mastering time and visualization efforts. Hence, the paper explores the benefits of virtual reality relaxation techniques on users: reduction of negative emotions, stress, anxiety, depression, and pain, as well as improved relaxation and positive affect. The multisensorial approach used in virtual reality techniques is presented to explain the positive impacts on these techniques compared to traditional techniques. However, while touch stimulation is known for decades to be very efficient to relax users, reduce stress and induce positive emotions. However, tactile stimuli are under-exploited in VR reduction-stress interventions. This review focuses on touch and its benefits on stress and affect. Finally, this paper discusses and provides perspectives on the present and future of tactile stimuli in virtual reality tools used to reduce stress.